The bad Angel brothers : a novel - Theroux, Paul (Mariner Books, 2022)
"Cal has always lived in the shadow of his brother, Frank, a complicated narcissist who was doted upon by their mother and beloved by the girls in their hometown-including Cal's own girlfriends. In an attempt to escape Frank's insidious presence, Cal pursues a different kind of freedom in the world's wild spaces, prospecting for gold and precious minerals everywhere from the heat of the desert at the Mexican border to the Alaskan chill to the suffocating African mines, where he will meet the love of his life, Vida. Soon he is dripping in wealth, his pockets full of gold nuggets and emeralds, but the money means far less to him than his independence. To Frank, however, it's everything. As Cal's success grows, so too does Frank's influence in his affairs, the emotional vacuum he creates at the center of his little brother's life. And, ultimately, when Frank decides to commit the ultimate betrayal...Cal is left with only one, final solution" --